Antimicrobial activity of lactobacillus strains against uropathogens. Issue 10 (28th June 2016) - Shim, Yoon Hee; Lee, Seung Joo; Lee, Jung Won
Abstract: Background: The use of lactobacillus probiotics has been proposed as an alternative to prophylactic antibiotics for preventing urinary tract infection (UTI) in the era of antibiotic resistance. In this study, the antimicrobial activity of lactobacillus strains against uropathogens, was evaluated and compared with that of antibiotics. Methods: To evaluate inhibitory activities of lactobacilli against uropathogens, six lactobacillus strains ( L. gasseri, L. rhamnosus, L. acidophilus, L. plantarum, L. paracasei, L. acidophilus ) and four representative uropathogens of infantile UTI (extended‐spectrum beta‐lactamase [ESBL](−) Escherichia coli, ESBL(+) E. coli, Proteus vulgaris, Enterococcus fecalis ) were selected. Lactobacillus strain in vitro inhibition of each uropathogen was evaluated on MRS agar well diffusion assay and compared with that of commercial antibiotic discs. Results: Average inhibitory zone for each of the six lactobacillus strains against the four uropathogens showed slightly different but consistent inhibition (inhibitory zone diameter, 10.5–20.0 mm). This was different to that of the antibiotic discs, which had a wider range of inhibition (inhibitory zone diameter, <6.0–27.5 mm) depending on the uropathogen resistance pattern. The inhibitory zone of the six lactobacillus strains was between that of sensitive and resistant antibiotics ( P < 0.05). Conclusions: Lactobacillus strains had similar moderate antimicrobial activities against uropathogens. Further research is needed to ascertain the strains with the best probiotic potential.